LITERATURE REVIEW DETERMINATION OF THINKING SYSTEMS AND QUALITY OF ISLAMIC EDUCATION: PLANNING AND DEVELOPMENT ANALYSIS - Sujono Sujono (Dinasti International Journal of Management Science, 2022)
In this study, the author raises problems related to the variables of systematic thinking and the quality of Islamic education in Islamic education through the variables of the planning system and the development system. The meaning of Islamic education planning is very important in developing the progress of Islamic education, so that with careful planning it will produce quality Islamic education in quality Islamic education. In this study the authors used a descriptive qualitative research approach. And the results of this study are planning systems and development systems in Islamic education must be able to see how society will portray in the future, and it is the task of planning to adapt the education system. Therefore, the mechanism that is considered most suitable for Islamic Education Planning is to combine a top-down planning approach with bottom-up planning. So that the development system will directly participate in developing.